Echocardiographic findings in patients with atrial fibrillation evidenced in electrocardiographic monitorization (Research, Society and Development, 2021)
Atrial fibrillation (AF), a pathology characterized as heart’s electrical dysfunction with high morbidity and mortality, has a 2-3% global prevalence and causes two-fold increase in mortality. The transthoracic echocardiography exam (TTE) is an imaging method used in cardiology clinic with the aim of a morphological, functional and hemodynamic evaluation. This study had the objective to determine findings in patients with AF by analyzing the holter and TTE’s parameters, present the distribution pattern of the cardiac dimensions in these patients and correlate the presence of other descriptive alterations, which are not AF, between those in sinusal rhythm and AF. The holter of 3988 individuals were observed, those which had AF performed an TTE and their morphological findings were. The results were presented in punctual estimates and the dispersion measures were calculated by trust intervals of 95%. The two-tailed p value of